A realist synthesis of cross-border patient movement from low and middle income countries to similar or higher income countries - Jo Durham; Sarah J. Blondell (BMC, 2017)
Abstract Patient travel across borders to access healthcare is becoming increasingly common and widespread. Patients moving from high income to middle income countries for healthcare is well documented, with patients seeking treatments that are cheaper or more readily available than at home. Less well understood is when patients move from one low income country to another or from a low income country to a higher income country. In this paper, a realist review was undertaken to explore why, in what contexts and how patients from lower income countries travel to countries with the same, or more advanced, economies for planned healthcare. Based on an initial scoping of the literature and discussions with key informants, we generated an initial theory and set of propositions about why, how, who and in what contexts people cross international borders for planned healthcare. We then systematically located and synthesized (1) peer-reviewed studies from the Scopus, Embase, Web of Science and Econlit databases; (2) non-indexed reports using key informants and Google; and (3) papers from the reference lists of included documents, to glean supportive or contradictory evidence for our initial propositions. As we reviewed the literature and extracted our data, we drew on the work of Pierre Bourdieu to understand the interplay between material and non-material capital and cognitive processes in decisions to cross borders for healthcare. Patient travel was largely undertaken due to a lack of services in the home country and/or unacceptability of local services, with decisions on when, and where, to travel, usually made within the patient's social networks. They were able to travel via use of multiple resources, including social networks, economic and cultural capital, and habitus. Those patients with greater volumes of the aforementioned factors had greater healthcare options; however, even those with limited resources engaged in patient travel. Patient movement challenges traditional ways of thinking about public health and the notion of health systems contained within the nation state. Further research is needed to better understand the effects of patient travel, and how to harness the benefits of patient travel without exacerbating existing health inequalities.